Características das artérias carótidas de adolescentes saudáveis ao ultrassom com doppler - Jovita Lane Soares Santos Zanini (2012)
Cardiovascular diseases are the leading cause of death among general population and images studies have established an important tool for measuring cardiovascular risks. The intima-media thickness (IMT) of the carotid arteries measured by ultrasonography has been evaluated in numerous studies among children and adolescents, proving to be an independent predictor of atherosclerosis and future cardiovascular events. Studies on carotid arteries dopplersonographic characteristics can help us better understand the etiology of the IMT increase clearly noted in individuals with cardiovascular risk factors once hemodynamic damage to the arterial wall is considered the most important event that triggers medio intimal thickening. However, one of the actual difficulties is the lack of definition of normal parameters for ultrasound (U.S.) of carotid Doppler in the pediatric population. The main goal of the study was to describe the characteristics of normality on the exam among healthy Brazilian adolescents. A cross-sectional study was conducted by using clinical, laboratory and ultrasound in 61 healthy adolescents (10-20 years), with no risk factor for cardiovascular disease. The average age of subjects was 14 years ± 2.6 years and 62.3% of the adolescents were females. No subject was a smoker. Serum glucose, lipid profile and blood pressure were within normal values for their age and sex. The ultrasound examinations were performed on Philips equipment, model HD11XE, equipped with a linear, high-resolution, multi frequency transducer adjusted to 12 MHzs. Tests followed the recommendations of the Consensus statement from the American Society of Echocardiography Carotid Intima-media Thickness Task Force. At the ultrasound evaluation, the average IMT at the Common Carotid Artery (CCA) was 0.51 mm on both sides with a standard deviation of 0.05 mm at the right and 0.04 mm at the left side. At the color Doppler study, every evaluated participant had no atherosclerotic plaques and laminar flow pattern. Velocity values of systolic peaks, minimum diastolic velocity, average velocity, systole/diastole relation, resistiveindex and pulsatility index were described. This is the first study that describes the normal parameters for carotid ultrasound with Doppler among Brazilian adolescents. This is also the bigger adolescents sample study, described in the main databases, in which all subjects underwent clinical and laboratory evaluations to certify they were healthy and without cardiovascular risk factors, and analyzing the association between IMT and pubertal stage according to Tanners criteria. It was observed that the IMT is greater in male adolescents. IMT increases as adolescents get older, and according to their pubertal stage and the size of the CCA, on both sides. The results of this study suggest that the increase of IMT at the carotid artery of healthy adolescents is related to normal physiological growth and may be used as a preliminary screening tool to evaluate risk factors for future cardiovascular events.